RAACS 2023 Competition for Medals and Diplomas - Bush, Dmitry (project baikal, 2023)
The article describes the new rules of the competition for medals and diplomas. It highlights the advantages of the new procedure and increased activity of applicants and voters. It also presents the winners of the competition.